STUDI KOMPARATIF TENTANG MAHRAM HAJI BAGI WANITA PERSPEKTIF 4 IMAM MADZHAB - Maula, Fika Ni’matul (Hujjah: Jurnal Ilmiah Komunikasi dan Penyiaran Islam, 2022)
This study examines how comparative studies of mahram hajj for women are based on four madhabs. Descriptive research is the research that researchers use in this study. Researchers describe facts, data and information obtained from literature studies such as books, journals to research results related to topics, research. In this study, it was explained that if a woman wants to perform Hajj or Umrah, according to the majority of scholars, she must travel with her mahram. Hanafi and Hanbali scholars argue that a woman should be accompanied by her husband either her husband or mahram. However, the Shafi'i and Maliki schools gave a dispensation in the hajj journey, namely a dispensation based on the concept of necessity. Adhering to the opposite position, Shafi'i argued that the presence of mahram was unnecessary; rather, the main requirement is the safety and security of women. According to those who adhere to the Shafi'i school, if a woman's safety is ensured by the presence of her husband, mahram or even a trustworthy woman, then she should be allowed to travel. Meanwhile, maliki madzhab does not demand the presence of mahram as long as his safety is guaranteed.